2018
DOI: 10.1007/s11524-018-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Sexual Coercion among People Who Inject Drugs (PWID) in Los Angeles and San Francisco, CA

Abstract: Experiences of coerced or forced sex have been associated with risk for HIV infection for all adults and may be more common for gays, lesbians, bisexuals (GLB) and people who inject drugs (PWID). In this study, we explored factors associated with prior 12-month experiences of forced or coerced sex among a sample of PWID, with a focus on sexual orientation and gender. PWID (N = 772) from Los Angeles and San Francisco were recruited using targeted sampling methods in 2011-2013 and surveyed on a range of items re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…rape) emerged as a common experience among some participants in this sample, in the context of both transactional and non-transactional sex. Prior research has found that female PWID, and in particular, female PWID who engage in sex work, are disproportionately impacted by sexual violence (Williams, Dangerfield, Kral, Wenger, & Bluthenthal, 2019). As victims of rape and other forms of sexual violence, they may not have agency over condom use (Medina-Perucha et al, 2019); as such, interventions focused on condom use without PrEP may still render some PWID, particularly female PWID who engage in sex work, vulnerable to HIV infection in instances of sexual coercion and violence.…”
Section: Discussionmentioning
confidence: 99%
“…rape) emerged as a common experience among some participants in this sample, in the context of both transactional and non-transactional sex. Prior research has found that female PWID, and in particular, female PWID who engage in sex work, are disproportionately impacted by sexual violence (Williams, Dangerfield, Kral, Wenger, & Bluthenthal, 2019). As victims of rape and other forms of sexual violence, they may not have agency over condom use (Medina-Perucha et al, 2019); as such, interventions focused on condom use without PrEP may still render some PWID, particularly female PWID who engage in sex work, vulnerable to HIV infection in instances of sexual coercion and violence.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the US is experiencing increases in acute hepatitis C virus (HCV) infections related to injection drug use (Zibbell et al, 2018), indicating that PWID are engaging in injection practices that increase risk for HIV transmission. Importantly, PWID face a dual risk for HIV from injection and sexual behaviors (Hill et al, 2018;Kral et al, 2001;Neaigus et al, 2013;Strathdee & Sherman, 2003), including transactional sex (Astemborski, Vlahov, Warren, Solomon, & Nelson, 1994;Jenness et al, 2011;Rondinelli et al, 2009) and forced sex (Williams, Dangerfield, Kral, Wenger, & Bluthenthal, 2018). This may be why there is a higher prevalence of sexually transmitted infections among PWID compared to the general population (Roth et al, 2016), leading to a growing need to prevent infectious disease spread among PWID.…”
Section: Introductionmentioning
confidence: 99%
“…There is clear evidence that sharing needles and syringes is a direct route for transmission of HIV-1 in 10 new HIV infections in the United States is among people who inject drugs (PWID) [1]. In addition to injection risk, PWID more frequently experience sexual coercion, sexual violence, and condomless sex, increasing risk of sexual transmission of HIV [2,3]. A culture of sharing injection equipment and high risk sexual behaviors results in PWID's having 22 times the risk of HIV infection compared to the population overall [4].…”
Section: Introductionmentioning
confidence: 99%